Integrated Marketing Communication Effects on Prospective Students’ Enrollment Decisions: Brand Image and Trust Mediation - Tsanin, M.; Masrifah, Lia Hilyatul; Fajriyah, Farah (Management Analysis Journal, 2026)
The study examines the influence of Integrated Marketing Communication (IMC) on prospective students’ enrollment decisions through the mediating roles of brand image and brand trust. Increasing competition in the higher education sector has positioned private higher education institutions as market-oriented service providers, requiring effective strategies to influence prospective students’ enrollment decisions. Drawing on a consumer behavior perspective, this study adopts a quantitative approach using survey data from 266 respondents, analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that IMC does not have a significant direct effect on prospective student enrollment decisions, but exerts strong positive effects on brand image and brand trust, both of which significantly influence prospective student enrollment decisions. Furthermore, IMC indirectly affects prospective student enrollment decisions through these mediators, confirming a full mediation mechanism. This study contributes to the IMC literature by demonstrating that communication effectiveness operates through brand-based perceptual and relational mechanisms rather than direct behavioral influence. From a managerial perspective, the findings suggest that higher education institutions should strategically design integrated and consistent communication efforts that reinforce institutional credibility, strengthen brand image, and build trust across multiple touchpoints to effectively drive prospective student enrollment decisions.